2022
DOI: 10.3389/fneur.2022.963624
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-early endovascular treatment improves prognosis in High grade aneurysmal subarachnoid hemorrhage: A single-center retrospective study

Abstract: BackgroundThe long-term survival prognosis of patients with high-grade (Hunt-Hess grade IV–V or World Federation of Neurosurgical Societies grade IV–V) aneurysmal subarachnoid hemorrhage (aSAH) is generally poor, and the association between endovascular treatment timing and the prognosis of high-grade aSAH has not been explored in depth. This retrospective cohort study aimed to determine whether endovascular treatment within 24 h of high-grade aSAH is associated with a better prognosis.MethodsWe retrospectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Philips et al ( 13 ) demonstrated that in their mixed surgical and endovascular series, the patients treated within 24 h after symptom onset had a better clinical outcome at 6 months. These data were confirmed by Consoli et al ( 14 ), who demonstrated that hyper-early endovascular treatment within 12 h after SAH is not associated with a lower morbidity or a better clinical outcome with respect to treatment after 12 h. Recently, Buscot et al ( 15 ) and Wu et al ( 16 ) showed that best clinical outcomes were achieved treating the patients at ~12.5 h.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…Philips et al ( 13 ) demonstrated that in their mixed surgical and endovascular series, the patients treated within 24 h after symptom onset had a better clinical outcome at 6 months. These data were confirmed by Consoli et al ( 14 ), who demonstrated that hyper-early endovascular treatment within 12 h after SAH is not associated with a lower morbidity or a better clinical outcome with respect to treatment after 12 h. Recently, Buscot et al ( 15 ) and Wu et al ( 16 ) showed that best clinical outcomes were achieved treating the patients at ~12.5 h.…”
Section: Introductionmentioning
confidence: 65%
“…In 2013, the European Stroke Organization underlined that the treatment should be aimed at least within 72 h after onset of first symptoms (4). Only few studies have focused on the best timing of treatment after SAH and most of them included only surgical clipping or both surgical and endovascular treatments (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). The definition of hyper-early, early, and delayed treatment varies widely in the different studies and their results are contradictory.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, numerous prediction models have been extensively developed to forecast the clinical outcomes in high-grade aSAH patients [ 4 ]. However, the majority of these models rely on conventional algorithms with limited clinical features.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, surgical intervention was done within seven days of the event, but researchers showed that patients experienced better outcomes if it was done within the first 72 hours [7,8]. Furthermore, evidence shows improved outcomes in patients who underwent ultra-early surgical intervention within 24 hours of ictus [9][10][11]. This case report concerns a 49-year-old male who underwent ultra-early surgical intervention after an aSAH rebleed and had excellent functional recovery during his six-month post-operative visit.…”
Section: Introductionmentioning
confidence: 99%